Artur Hącia, Psychiatra i jego misja w nauczaniu Kościoła, Poligrafi a Salezjańska, Lublin 2017, s. 449. - Derdziuk, Andrzej (Teologia i Moralność, 2018)
Artur Hącia, Psychiatra i jego misja w nauczaniu Kościoła, Poligrafi a Salezjańska, Lublin 2017, s. 449.